Impact investing in Africa: a 2024 analytical map - (:unkn) unknown (My University, 2024)
Impact investing has attracted considerable interest from both academics and practitioners, regardless of their direct involvement in the practice. Despite its growing visibility, there is a lack of evidence on impact investing in Africa. This report seeks to fill that gap. First, we clarify the definition of impact investing and its specificities in Africa. Second, we use a newly developed database of 255 impact investors operating on the African continent to examine the dynamics and characteristics of the sector in Africa. The Chair’s analysis provides several policy recommendations for better financing, enhanced financial sustainability, and improved quality of impact assessment and measurement.
Keywords: African Research